Domestic violence surveillance system: a model Sistema de vigilancia de violencia doméstica: un modelo - Rafael Espinosa; María Isabel Gutiérrez; Jorge Humberto Mena-Muñoz; Patricia Córdoba (Instituto Nacional de Salud Pública, 2008)
OBJECTIVE: To develop a domestic violence surveillance system. MATERIAL AND METHODS: The strategies included implementation of a standard digitalized reporting and analysis system along with advocacy with community decision makers, strengthening inter-institutional attention networks, consultation for constructing internal flow charts, sensitizing and training network teams in charge of providing health care in cases of domestic violence and supporting improved public policy prevention initiatives. RESULTS: A total of 6 893 cases were observed using 2004 and 2005 surveillance system data. The system reports that 80% of the affected were women, followed by 36% children under 14 years. The identified aggressors were mainly females' partners. The system was useful for improving victim services. CONCLUSIONS: Findings indicate that significant gains were made in facilitating the attention and treatment of victims of domestic violence, improving the procedural response process and enhancing the quality of information provided to policy-making bodies. OBJETIVO: Desarrollar un sistema de vigilancia sobre violencia doméstica. MATERIAL Y MÉTODOS: Las estrategias incluyeron la implementación de un sistema de análisis y reporte digitalizado estándar, a la par de hacer conciencia entre los tomadores de decisiones a nivel comunitario, fortalecer redes de atención interinstitucionales, consultoría para el diseño de diagramas de flujo internos, equipos de sensibilización y entrenamiento a cargo de proveer cuidados de salud en casos de violencia doméstica y de dar a poyo a iniciativas de prevención como parte de políticas públicas mejoradas. RESULTADOS: Se observó un total de 6893 casos a partir de datos de 2004 y 2005 de un sistema de vigilancia. El sistema informa que 80% de las víctimas fueron mujeres, seguidas de 36% de niños menores de 14 años. Los agresores identificados fueron principalmente los compañeros de las mujeres. El sistema resultó útil para mejorar los servicios a las víctimas. CONCLUSIONES: Los hallazgos indican que se lograron mejoras significativas en cuanto a facilitar la atención y tratamiento de las víctimas de violencia doméstica, mejorando el proceso de respuesta procedimental y la calidad de la información brindada a los organismos responsables de elaborar políticas.